Effects of Alachlor and Glyphosate on Development of Glomus Mosseae and its Symbiotic Association with Peanut - Pasaribu, Askif (2004)
Data on the effect of herbicides on vesicular-arbuscular mycorrhiza (VAM) symbiosis is still lacking as compared to fungicides. This study aims to evaluate the effect of alachlor (soil acting herbicide) and glyphosate (foliage acting herbicides) on Glomus mosseae (VAM fungus) growth phases directly and indirectly on its symbiotic association with peanut plant. Laboratory experiment was carried out to determine the effects of herbicides on spore germination and hyphal growth of G. mosseae. The recommended rates of alachlor for soil and water agar media are 3.6 μg ai g-1 soil and 24 μg ai mL-1 agar, and for glyphosate are 2.16 μg ae g-1 soil and 14 μg ae mL-1 agar, respectively. Alachlor at ten fold of the recommended rate significantly (P ≤ 0.01) reduced spore germination of G. mosseae by 36 and 43%, and hyphal length was reduced by 61and 83% in soil and water agar media, respectively. The application of alachlor at ten folds of the recommended rate (36 μg ai g-1) reduced the length of active external hyphae of G. mosseae by 40% (23.99 cm g-1). Alachlor at one and half of the recommended rate (5.4 μg ai g-1) decreased the development and succinate dehydrogenase (SDH) activity of internal hyphae of G. mosseae, and amount of mycorrhizal tissue. In contrast, glyphosate at all rates had no negative effects on spore germination and hyphal length of G. mosseae in both soil and water agar media, and also did not affect the external and internal hyphae. The effect of herbicides on G. mosseae symbiosis with peanut was also studied in the greenhouse. The adverse effects of alachlor on the mycorrhizal plants was greater than in non-mycorrhizal plants. The phosphorus concentration in the shoot was unaffected by alachlor in the non-mycorrhizal plant or by glyphosate in the mycorrhizal plant and vice versa. Alachlor and glyphosate did not affect P inflow into non-mycorrhizal plants. However, P inflow into mycorrhizal plant was increased by glyphosate application at 2.16 μg ae g-1 which gave 65.31 x 10-13 mol P m-1 s-1. It increased hyphal inflow of 41.48 x 10-13 mol P m-1 s-1, and consequently increased hyphal uptake from soil to be 479.72 from 48.04 x 10-13 mol P m-1 s-1 in control. The effect of G. mosseae on the persistence and degradation of herbicides in the soil showed that the rate of degradation of alachlor was higher in G. mosseae inoculated soil than in the uninoculated soil. Therefore, the persistence of alachlor in the soil was shortened by 6 days with the presence of G. mosseae. However, the persistence of glyphosate in the soil was unaffected by the presence of the fungi. The result of study showed that the type of herbicides and their rates are important factors mediating the effects of herbicides on G. mosseae and its symbiosis with peanut plant. The distinct growth phases of G. mosseae may differ in their tolerance to alachlor herbicide. There was an interaction between alachlor and G. mosseae which was indicated by the adverse effect on mycorrhizal plants, and evidence that the persistence of alachlor in the soil was shortened by the fungi. In contrast, glyphosate did not affect the growth phases of G. mosseae.